2020
DOI: 10.6004/jnccn.2020.7595
|View full text |Cite
|
Sign up to set email alerts
|

What’s in a Number? Examining the Prognostic and Predictive Importance of Platelet Count in Patients With Essential Thrombocythemia

Abstract: Essential thrombocythemia (ET) is a myeloproliferative neoplasm characterized by clonal overproduction of platelets and an increased risk of thrombohemorrhagic complications. Patients are risk stratified by driver mutation, age, and thrombotic history and treated to reduce the risk of thrombotic and hemorrhagic events. The significance of platelet number as a risk factor or treatment goal is unclear. Despite the preponderance of data failing to demonstrate an association, there exists a pervasive belief that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…According to current recommendations, cytoreductive treatment to lower platelet counts is indicated in patients with ET with additional risk factors for thrombosis, such as age > 60 years, previous thrombosis, and JAK2 V617F mutation 4 . However, the relationship between platelet count and thrombotic risk as well as the optimal platelet count target to prevent thrombosis remain controversial 43 . In our study, the b.i.d.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…According to current recommendations, cytoreductive treatment to lower platelet counts is indicated in patients with ET with additional risk factors for thrombosis, such as age > 60 years, previous thrombosis, and JAK2 V617F mutation 4 . However, the relationship between platelet count and thrombotic risk as well as the optimal platelet count target to prevent thrombosis remain controversial 43 . In our study, the b.i.d.…”
Section: Discussionmentioning
confidence: 83%
“…4 However, the relationship between platelet count and thrombotic risk as well as the optimal platelet count target to prevent thrombosis remain controversial. 43 In our study, the b.i.d. aspirin regimen seemed to blunt the variable impact of cytoreduction on platelet count and sTXB 2 .…”
Section: Articlementioning
confidence: 78%
“…1,2 A recent international physician survey disclosed marked inconsistencies on management of low risk ET with ExT ≥1500 x 10 9 /L, arising from concerns regarding an increased risk of thrombosis and/or bleeding. 3,4 The pro-thrombotic or pro-hemorrhagic impact of thrombocytosis was studied in a prospective multicenter cohort of 776 ET patients from the randomized PT-1 trial and found no association between blood counts at diagnosis and future complications. However, platelet count outside of the normal range (> 450 x 10 9 /L) during follow-up was associated with an immediate risk of major hemorrhage but not thrombosis.…”
Section: To the Editormentioning
confidence: 99%
“…[9][10][11] In addition, interpretation of findings from prior reports is confounded by variability in platelet count thresholds utilized to define ExT. 4 The objectives for the current study in ET included i) estimation of prevalence of ExT ≥1500 x 10 9 /L at time of diagnosis, ii) phenotypic and genotypic characterization of patients presenting with ExT ≥1500 x 10 9 /L, and iii) determination of impact on thrombotic and bleeding events, in the context of other risk factors and specific therapy.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation